Gradual extinction reduces reinstatement - Shiban, Youssef; Wittmann, Jasmin; Weißinger, Mara; Mühlberger, Andreas (Frontiers in Behavioral Neuroscience, 2015)
The current study investigated whether gradually reducing the frequency of aversive stimuli during extinction can prevent the return of fear. Thirty-one participants of a three-stage procedure (acquisition, extinction and a reinstatement test on day two) were randomly assigned to a standard extinction (SE) and gradual extinction (GE) procedure. The two groups differed only in the extinction procedure. While the SE group ran through a regular extinction process without any negative events, the frequency of the aversive stimuli during the extinction phase was gradually reduced for the GE group. The unconditioned stimulus was an air blast (5 bar, 10 ms). A spider and a scorpion were used as conditioned stimuli. The outcome variables were contingency ratings and physiological measures (skin conductance response and startle response). There were no differences found between the two groups for the acquisition and extinction phases concerning contingency ratings, SCR, or startle response. Gradual extinction compared to standard extinction significantly reduced the return of fear in the reinstatement test for the startle response but not for skin conductance response or contingency ratings. This study was successful in translating the findings in rodent to humans. The results suggest that the gradual extinction process is suitable for increasing the efficacy of fear extinction.